Analisis Pembelajaran Ips Kelas V Tema 6 Subtema 1 Pembelajaran 1 Dengan Menggunakan Strategi Dua Tinggal Dua Tamu Dan Card Sort - Muhammad Majdi (STAI AL FALAH Banjarbaru, 2021)
The author analyzes social studies learning using the Two Stay Two Stray strategy and the Card Sort strategy in the Thematic Book of Class V Theme 6 Human and Animal Organs. The underlying foundation is the lack of engagement strategies with a HOTS mindset. Social studies material in collaboration with these 2 learning strategies is oriented to the HOTS mindset. Methodology This research uses qualitative research with an inductive approach. Data was obtained by observation and interviews as well as important notes. The research location is at MIS Al Islamiyah Bangkar, Muara Uya District, Tabalong Regency, South Kalimantan Province. The subject in this study was the homeroom teacher of MIS Al Islamiyah Bangkar. The application in learning the two-stay-two-guest strategy is asking to form groups of 4 people. Their task Two people visit another group while the other two stays in the group to entertain other visiting groups. while the card sort strategy uses 2 media, namely cardboard as a sorting medium and a magic bag to shuffle the material when it comes to the fore. The implication is in interesting learning activities and a HOTS-oriented mindset. Strategy Two, there are only two guests and the Card sort strategy has a good correlation with basic competencies and indicators in the thematic book Theme 6 Human and Animal Organs, sub-theme 1 Human Body learning 1. Applying these 2 strategies has advantages in responsibility, cooperation, solving problems, learning motivation, and learning evaluation. These two strategies have the advantage of creating high thinking so that students are active in thinking. Students can develop their abilities or ways of thinking so that they can master higher-order thinking skills (HOTS). Keywords: Social Studies Learning Analysis, Strategy two stay two guests, strategy